Los derechos de la naturaleza vulnerados por la actividad minera dentro del bosque protector los cedros como sujeto de derechos - Moreno Coello, Mercedes Victoria (2025)
This comprehensive review addresses the violation of the rights of nature by allowing mining activities in the Los Cedros Protective Forest. The Mayor and the Attorney General of the Province of Imbabura, Cotacachi Canton, have filed a legal action against the Ministry of the Environment and the National Mining Company. This challenge focuses on the administrative decisions made by these entities, especially regarding the environmental registry and the environmental plan, since these actions grant concessions to the mining company and negatively affect natural rights. To address this problem, a critical legal and environmental analysis is proposed to clearly establish the legal regulations that safeguard and protect nature. This will allow us to identify how the right related to the Los Cedros Protective Forest has been omitted, thus harming environmental rights as dictated by ruling 1149-19-JP/21. To achieve this objective, a qualitative methodology is applied, using documents, texts, previous works, and environmental legal regulations as the theoretical foundation to achieve an adequate legal basis. Finally, this investigation clearly demonstrates the lack of compensation for the peoples and communities affected by the damage and the lack of sanctions for environmental damage; and it highlights the conflict between the State's obligation to protect fragile ecosystems and adopt timely and effective environmental protection measures, and environmental regulations through environmental registration with its officials.